Formulation And Characterization Of Aceclofenac Loaded Bovine Serum Albumin Microspheres - PRAVEEN.B; MURALIDHAR RAO.R; MAHESH KUMAR.G; SUNIL KUMAR.K; SWETHA.G (International Journal of Pharma and Bio Sciences, 2011)
Controlled drug delivery systems designed to deliver drug, at predetermined rates for predefined periods of time, have been used to overcome the shortcoming of conventional drug formulations. Among the microparticulate system, microspheres have a special importance to target drugs and provide controlled release. Aceclofenac is a potent non-steroidal anti-inflammatory agent, and is widely used in the treatment of rheumatoid arthritis, osteoarthritis, and ankylosing spondylitis. Aceclofenac is administered in dose of 100mg 2-3 times daily, which leads to fluctuation in the drug blood level and dose related adverse effects. Multiple dosing also often results in poor compliance and inefficient therapy. Formulations of Aceclofenac microsphere prepared by suspension cross-linking method using albumin as polymer to prevent the gastric irritation and to achieve oral sustained / controlled release of the drug. Preformulation studies revealed that the drug Aceclofenac and the polymer albumin were satisfactorily compatible without any change in the chemical nature of the drug. In present study two formulations were formulated by using bovine serum albumin. The formulations were subjected to various evaluation parameters like % practical yield, actual drug content, entrapment efficiencies, particle size distribution and in-vitro release studies. The results of all parameters are tabulated and depicted graphically in the results and discussion section. The advantages of such controlled release formulations containing non-steroidal anti-inflammatory drugs (NSAIDs) over the conventional dosage forms have been reported. Such formulations minimize the gastric irritant side effects of the conventional NSAID preparations.